Priming the Representation of Left-Dominant Sandhi Words: A Shanghai Dialect Case Study. (June 2020) - Yan, Hanbo; Chien, Yu-Fu; Zhang, Jie
The paper aims to examine how the acoustic input (the surface form) and the abstract linguistic representation (the underlying representation) interact during spoken word recognition by investigating left-dominant tone sandhi, a tonal alternation in which the underlying tone of the first syllable spreads to the sandhi domain. We conducted two auditory-auditory priming lexical decision experiments on Shanghai left-dominant sandhi words with less-frequent and frequent Shanghai users, in which each disyllabic target was preceded by monosyllabic primes either sharing the same underlying tone, surface tone, or being unrelated to the tone of the first syllable of the sandhi targets. Results showed a surface priming effect but not an underlying priming effect in younger speakers who used Shanghai less frequently, but no surface or underlying priming effect in older speakers who used Shanghai more often. Moreover, the surface priming did not interact with speakers' familiarity ratings to the sandhi targets. These patterns suggest that left-dominant Shanghai sandhi words may be represented in the sandhi form in the mental lexicon. The results are discussed in the context of how phonological opacity, productivity, the non-structure-preserving nature of tone spreading, and speakers' semantic knowledge influence the representation and processing of tone sandhi words.